Methane sources in arctic thermokarst lake sediments on the North Slope of Alaska. Issue 2 (22nd January 2015) - Matheus Carnevali, P. B.; Rohrssen, M.; Williams, M. R.; Michaud, A. B.; Adams, H.; Berisford, D.; Love, G. D.; Priscu, J. C.; Rassuchine, O.; Hand, K. P.; Murray, A. E.
Abstract The permafrost on the North Slope of Alaska is densely populated by shallow lakes that result from thermokarst erosion. These lakes release methane (CH4) derived from a combination of ancient thermogenic pools and contemporary biogenic production. Despite the potential importance of CH4 as a greenhouse gas, the contribution of biogenic CH4 production in arctic thermokarst lakes in Alaska is not currently well understood. To further advance our knowledge of CH4 dynamics in these lakes, we focused our study on (i) the potential for microbial CH4 production in lake sediments, (ii) the role of sediment geochemistry in controlling biogenic CH4 production, and (iii) the temperature dependence of this process. Sediment cores were collected from one site in Siqlukaq Lake and two sites in Sukok Lake in late October to early November. Analyses of pore water geochemistry, sedimentary organic matter and lipid biomarkers, stable carbon isotopes, results from CH4 production experiments, and copy number of a methanogenic pathway‐specific gene (mcrA) indicated the existence of different sources of CH4 in each of the lakes chosen for the study. Analysis of this integrated data set revealed that there is biological CH4 production in Siqlukaq at moderate levels, while the very low levels of CH4 detected in Sukok had a mixed origin, with little to no biological CH4 production. Furthermore, methanogenic archaea exhibited temperature‐dependent use of in situ substrates for methanogenesis, and the amount of CH4 produced was directly related to the amount of labile organic matter in the sediments. This study constitutes an important first step in better understanding the actual contribution of biogenic CH4 from thermokarst lakes on the coastal plain of Alaska to the current CH4 budgets.